2016
DOI: 10.4238/gmr.15038805
|View full text |Cite
|
Sign up to set email alerts
|

Expression of M3 acetylcholine receptor in asthmatic mice and bronchial airway remodeling prediction

Abstract: ABSTRACT. This study aimed to investigate the role of M 3 acetylcholine receptor (M 3 -AChR) expression in airway remodeling. Additionally, we aimed to evaluate the effects of ipratropium bromide solution inhaled in an early phase of asthma on airway remodeling in ovalbumin (OVA)-sensitized and challenged mice. Thirty BALB/c mice were divided into three groups, namely, control group (saline sensitized/challenged mice), asthma group (OVA sensitized/challenged mice), and treatment group (OVA sensitized/challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Holownia et al [38] found that tiotropium could increase cytosolic ChRM3 protein level in induced sputum cells of COPD patients. Similarly, ipratropium bromide, another common acetylcholine receptor antagonist, could upregulate ChRM3 expression in bronchial walls of an asthmatic murine model [39]. The results of existing studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Holownia et al [38] found that tiotropium could increase cytosolic ChRM3 protein level in induced sputum cells of COPD patients. Similarly, ipratropium bromide, another common acetylcholine receptor antagonist, could upregulate ChRM3 expression in bronchial walls of an asthmatic murine model [39]. The results of existing studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%